2013
DOI: 10.1105/tpc.112.108753
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Text Mining in Data Integration and Network Biology for Plant Research: A Case Study onArabidopsis   

Abstract: Despite the availability of various data repositories for plant research, a wealth of information currently remains hidden within the biomolecular literature. Text mining provides the necessary means to retrieve these data through automated processing of texts. However, only recently has advanced text mining methodology been implemented with sufficient computational power to process texts at a large scale. In this study, we assess the potential of large-scale text mining for plant biology research in general a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
(69 reference statements)
0
21
0
Order By: Relevance
“…These methods were applied on all 22 million PubMed abstracts and 460,000 PubMed Central open-access full-text articles available through the text-mining resource EVEX (Van Landeghem et al, 2013a, 2013b. Texts were restricted to studies on Arabidopsis through a keyword search, and articles that mentioned abiotic stress, salt stress, osmotic stress, or oxidative stress were identified, performing case-insensitive matching throughout the article text and allowing for lexical variations such as hyphens.…”
Section: Text Miningmentioning
confidence: 99%
See 1 more Smart Citation
“…These methods were applied on all 22 million PubMed abstracts and 460,000 PubMed Central open-access full-text articles available through the text-mining resource EVEX (Van Landeghem et al, 2013a, 2013b. Texts were restricted to studies on Arabidopsis through a keyword search, and articles that mentioned abiotic stress, salt stress, osmotic stress, or oxidative stress were identified, performing case-insensitive matching throughout the article text and allowing for lexical variations such as hyphens.…”
Section: Text Miningmentioning
confidence: 99%
“…To assess which concentrations are commonly used in literature, PubMed abstracts and open-access articles from PubMed Central, available through the text-mining resource EVEX (Van Landeghem et al, 2013a, 2013b, were scanned for keywords related to salt, osmotic, and oxidative stress in Arabidopsis, and concentrations of NaCl, mannitol, sorbitol, and H 2 O 2 used in stress assays were automatically extracted, followed by manual curation. Our analysis showed that most studies use very severe stress conditions, with median concentrations of 150 mM NaCl, 300 mM mannitol/sorbitol, and 10 mM H 2 O 2 (Fig.…”
Section: Most Studies Use Very High Concentrations Of Stress-inducingmentioning
confidence: 99%
“…The utilization of network theory and related methodologies to analyze various forms of large-scale data has become an essential part of systems biology (Albert, 2007;Lee et al, 2010;Ferrier et al, 2011;Hwang et al, 2011;Bassel et al, 2012;Li et al, 2012;Kleessen et al, 2013;Van Landeghem et al, 2013). Among the network analytical techniques that have recently been applied in biology, differential network (DN) analysis has shown robustness, which is evident in its ability to identify the DNA damage response genes in yeast (Bandyopadhyay et al, 2010;Califano, 2011), body weight-related genes in mice (Fuller et al, 2007;Gill et al, 2010), T cell differentiation-related genes in human (Elo et al, 2007), and human disease-relevant genes (Hudson et al, 2009;Amar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Text mining can retrieve these data, but as the body of information grows, the feasibility of manual annotation decreases. However, advanced textmining methodology has recently been implemented (Van Landeghem et al, 2013), including work to collate information about specific tissues or processes in a readily accessible format. For example, the more than 1,300 articles that describe processes related to root hair cells would require extensive time and effort to extract relevant information by a traditional literature review (Kwasniewski et al, 2013).…”
Section: Tools and Resources Available For Root System Biology Studiesmentioning
confidence: 99%